PATHOGEN FOUND COMMONLY ON BLOOD CULTURE OF PATIENTSTREATED FOR ACUTE MYELOID LEUKEMIAIN FEBRILE NEUTROPENIC STATE AND THEIR SENSITIVITY TO DIFFERENT ANTIBIOTICS - Muhammad Khurram Islam; Tahir Mehmood; Kausar Bano; Muhammad Akram; Tehreem Fatima (Journal of University Medical & Dental College, 2019)
Objective: To determine the frequency of gram positive and negative pathogens and to assess the cultural sensitivity of pathogens present in blood stream of patients presenting with Febrile Neutropenia in Acute Myeloid Leukemia (AML). Material and Methods: Thisdescriptive case series study was conducted on 100acute myeloid leukemic patients at Department of Oncology Jinnah Hospital Lahore from May 2017 to November 2017. The patients aged 20-60 years and of either gender presenting with febrile neutropenia and taking chemotherapy for atleast 2 months were included. Patients with recurrent blood stream infection and already on quinolone prophylaxiswereexcluded. Then blood samples were obtained by using 3cc BD syringe. All samples were stored in sterile container and sent to the pathology laboratory of hospital. Reports were assessed and type of pathogen (gram negative or positive and organism) and its sensitivity with antibiotics was noted. Results: There were 82% Gram negative organisms while Gram positive were only 18%. Gram negative cultures included 36% Escherichia coli, 14.0% Klebsiella pneumonia, 13.0% Klebsiella spp., 15.0% Pseudomonas aeruginosa and 4.0% Pseudomonas spp. Gram positive isolates had 16% Staphylococcus aureus. Cultural sensitivity of pathogens present in blood stream of AML patients presenting with febrile neutropenia showed sensitive to piperacillin/tazobactam (53%), amikacin (85%), and carbapenem group (59%) while it was exhibiting very good sensitivity to cefoperazone/sulbactam (93%) and vancomycin (91%). Conclusion: This study concluded that thefrequency of gram negative pathogens in blood stream of patients presenting with febrile neutropenia in acute myeloid leukemia is very high and also cefoperazone is the most sensitive antibiotic.